2014
DOI: 10.1038/jid.2014.63
|View full text |Cite
|
Sign up to set email alerts
|

Patched 1 and Patched 2 Redundancy Has a Key Role in Regulating Epidermal Differentiation

Abstract: The Patched 1 (Ptch1) receptor has a pivotal role in inhibiting the activity of the Hedgehog (Hh) pathway and is therefore critical in preventing the onset of many human developmental disorders and tumor formation. However, the functional role of the mammalian Ptch2 paralogue remains elusive, particularly the extent to which it contributes to regulating the spatial and temporal activity of Hh signaling. Here we demonstrate in three independent mouse models of epidermal development that in vivo ablation of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 47 publications
1
35
0
Order By: Relevance
“…We recently proposed that the difference in outcome between a tumorigenic Ptch1-deficient phenotype and the loss of epidermal specification and differentiation observed in Ptch1;Ptch2-deficient skin is attributable to differences in the amplitude of Hh signalling activity subsequently evoking distinct cellular responses (Adolphe et al, 2014). In order to define the amplitude of pathway activity we used single molecule fluorescent in situ hybridization (smFISH) to quantitate RNA transcript density of the Hh target genes Ptch1 and Gli1 in individual cells (Figure 1a) (Junker et al, 2014;Raj et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently proposed that the difference in outcome between a tumorigenic Ptch1-deficient phenotype and the loss of epidermal specification and differentiation observed in Ptch1;Ptch2-deficient skin is attributable to differences in the amplitude of Hh signalling activity subsequently evoking distinct cellular responses (Adolphe et al, 2014). In order to define the amplitude of pathway activity we used single molecule fluorescent in situ hybridization (smFISH) to quantitate RNA transcript density of the Hh target genes Ptch1 and Gli1 in individual cells (Figure 1a) (Junker et al, 2014;Raj et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Thus the level of activity generated in Ptch1-deficient cells acts to define the tumorigenic threshold of Hh signalling in skin. In contrast, we have recently shown that concomitant inactivation of both Ptch1 and Ptch2 during epidermal development leads to loss of interfollicular epidermis (IFE), HF and sebaceous gland specification and differentiation (Adolphe et al, 2014). Taken together, these data indicate that different amplitudes of Hh signalling activity drive distinct cellular responses and cell fate decisions in the skin.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 91%
See 1 more Smart Citation
“…To overcome this problem, two groups, including my group, generated mutant mice with epidermis-specific loss of aPKCλ using K5-Cre or K14-Cre mice [22,23]. Although, in a strict sense, the distribution of K14-Cre transgene activity differs from that of K5-Cre transgene activity in the epidermis and hair follicle [25,26], both mutant mice showed similar skin phenotypes. Thus, hereafter, when referring to findings common to both conditional knockout (cKO) mice, the term mutant mice or aPKCλ cKO mice is used, and when referring to findings obtained in the mutant mice associated with K5-Cre or K14-Cre individually, the term K5-cKO or K14-cKO mice is used, respectively.…”
Section: Progressive Hair Lossmentioning
confidence: 99%
“…In vertebrates, HH-dependent patterning requires not only PTCH1, but two additional, vertebrate-specific feedback antagonists: the PTCH1 homologue, PTCH2, and HHIP1 (Motoyama et al, 1998;Carpenter et al, 1998;Chuang and McMahon, 1999;Koudijs et al, 2005Koudijs et al, , 2008. PTCH1 and PTCH2 act redundantly in multiple cells and tissues, including the developing skin (Adolphe et al, 2014;Alfaro et al, 2014). However, HH-dependent ventral neural patterning is severely disrupted after the combined removal of PTCH2, HHIP1, and PTCH1 feedback inhibition (Milenkovic et al, 1999;Jeong and McMahon, 2005;Holtz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%